2020
DOI: 10.1080/15384047.2020.1763148
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential therapeutic targets in urothelial bladder carcinoma of Chinese population by targeted next-generation sequencing

Abstract: Patients with urothelial carcinoma (UC) of the bladder have a high risk of death in China. However, a lack of comprehensive molecular profiling in Chinese Han population hinders the development of targeted therapies for bladder cancer. In our present study, we collected fresh bladder tumors from low-grade (T1, N0, M0, G1) non-muscle invasive bladder cancer (NMIBC) patients (n = 16) and high-grade (T2-4, N0, M0, Gx) muscle-invasive bladder cancer (MIBC) patients (n = 16) with their paired normal bladder tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 50 publications
(56 reference statements)
1
10
0
Order By: Relevance
“…Data from TCGA Research Network showed that TP53 (49%), MLL2 (27%), ARID1A (25%), KDM6A (24%), PIK3CA (20%), EP300 (15%), CDKN1A (14%), RB1 (13%), ERCC2(12%), FGFR3 (12%), STAG2 (11%) were the most frequently mutated genes in BCa ( The Cancer Genome Atlas Research Network, 2014 ). Data of 103 China BCa samples downloaded from International Cancer Genome Consortium (ICGC) database showed that TP53 (27.2%), KDM6A (24.3%), FGFR3 (16.5%), HRAS (15.5%), ERBB2 (13.6%), CREBBP (12.6%), ERCC2 (12.6%), ARID1A (11.7%), and XIRP2 (10.7%) were the top mutated genes ( Wang et al, 2020 ). One recent study conducted by Wang T et al performed targeted NGS in 32 BCa samples showed that FGFR3 (31.3%), KMT2D (18.8%), TP53 (12.5%), ARID1A (12.5%), AKT1 (12.5%), KDM6A (9.4%), STAG2 (9.4%), and LRP1B (9.4%) were the most frequently mutated genes in Chinese BCa patients ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Data from TCGA Research Network showed that TP53 (49%), MLL2 (27%), ARID1A (25%), KDM6A (24%), PIK3CA (20%), EP300 (15%), CDKN1A (14%), RB1 (13%), ERCC2(12%), FGFR3 (12%), STAG2 (11%) were the most frequently mutated genes in BCa ( The Cancer Genome Atlas Research Network, 2014 ). Data of 103 China BCa samples downloaded from International Cancer Genome Consortium (ICGC) database showed that TP53 (27.2%), KDM6A (24.3%), FGFR3 (16.5%), HRAS (15.5%), ERBB2 (13.6%), CREBBP (12.6%), ERCC2 (12.6%), ARID1A (11.7%), and XIRP2 (10.7%) were the top mutated genes ( Wang et al, 2020 ). One recent study conducted by Wang T et al performed targeted NGS in 32 BCa samples showed that FGFR3 (31.3%), KMT2D (18.8%), TP53 (12.5%), ARID1A (12.5%), AKT1 (12.5%), KDM6A (9.4%), STAG2 (9.4%), and LRP1B (9.4%) were the most frequently mutated genes in Chinese BCa patients ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data of 103 China BCa samples downloaded from International Cancer Genome Consortium (ICGC) database showed that TP53 (27.2%), KDM6A (24.3%), FGFR3 (16.5%), HRAS (15.5%), ERBB2 (13.6%), CREBBP (12.6%), ERCC2 (12.6%), ARID1A (11.7%), and XIRP2 (10.7%) were the top mutated genes ( Wang et al, 2020 ). One recent study conducted by Wang T et al performed targeted NGS in 32 BCa samples showed that FGFR3 (31.3%), KMT2D (18.8%), TP53 (12.5%), ARID1A (12.5%), AKT1 (12.5%), KDM6A (9.4%), STAG2 (9.4%), and LRP1B (9.4%) were the most frequently mutated genes in Chinese BCa patients ( Wang et al, 2020 ). Wu S. et al ( Wu et al, 2019 ) found FGFR3, TP53, PIK3CA, ZFP36L1, HRAS, and KDM6A were frequently mutated in Chinese BCa patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,62,65 In addition, one study investigated RC48-ADC in HER2-positive patients evaluated by IHC and further confirmed by FISH. 11 In seven studies related to FGFR, five reported FGFR3 alterations, [68][69][70][71][72] one explored FGFR family alterations in UC patients, 73 and one investigated the landscape of FGF/ FGFR alterations in a large cohort of 12,737 cancer patients with a high prevalence of FGF/FGFR mutations | 15397 occurring in urinary tract cancer (52.7%, 145/275). 74 Various testing methods were applied, including sanger sequencing (n = 2), next-generation sequencing (NGS, n = 4), and whole-genome sequencing (n = 1).…”
Section: Treatment-related Biomarkers Among Chinese Populationmentioning
confidence: 99%